2001
DOI: 10.1090/s0002-9939-01-05819-1
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric numerical semigroups with arbitrary multiplicity and embedding dimension

Abstract: Abstract. We construct symmetric numerical semigroups S for every minimal number of generators µ(S) and multiplicity m(S), 2 ≤ µ(S) ≤ m(S) − 1. Furthermore we show that the set of their defining congruence is minimally generated by µ(S)(µ(S) − 1)/2 − 1 elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…We have posed a conjecture 3.3 in section 3 on the unboundedness of minimal number of generators of the defining ideal in arbitrary embedding dimension. Our results in section 4 generalizes the results proved in [9].…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…We have posed a conjecture 3.3 in section 3 on the unboundedness of minimal number of generators of the defining ideal in arbitrary embedding dimension. Our results in section 4 generalizes the results proved in [9].…”
Section: Introductionsupporting
confidence: 87%
“…Given an integer e ≥ 4, it is not completely understood whether the symmetry condition on Γ in embedding dimension e ensures that the minimal cardinality of a system of generators of σ defined above is a bounded function of e. This was answered in affirmative by Bresinsky for e = 4 in [2], and for certain cases of e = 5 in [3]. Rosales [9] constructed numerical semigroups for a given multiplicity m and embedding dimension e, which are symmetric, and showed that the cardinality of a minimal presentation of these semigroups is a bounded function of the embedding dimension e. In fact using the pertinent results obtained in [2], [5], [10], [12], one can compute the cardinality of a minimal presentation of a symmetric numerical semigroup with multiplicity m ≤ 8. This remains an open question in general, whether symmetry condition on the numerical semigroup e ≥ 5 imposes an upper bound on the cardinality of a minimal presentation of a numerical semigroup Γ.…”
Section: Introductionmentioning
confidence: 99%
“…In [36] the case a = e + 1 has been studies in detail and it has been proved that µ(p) is bounded. In [36] it has been shown that there are symmetric semigroups of this form, generalizing Roasales' construction in [46]. Our observations in [36] give rise to the following question:…”
Section: Betti Numbers and Their Unboundednesssupporting
confidence: 55%
“…Bresinski also proves in [8] that the cardinality for a minimal presentation of a symmetric numerical semigroup with embedding dimension four can only be three or five. It is conjectured in [36] that if S is a numerical semigroup with e(S) ≥ 3, then the cardinality of a minimal presentation for S is less than or equal to e(S)(e(S)−1) 2 − 1. Barucci [2] proves with the semigroup 19,23,29,31,37 that the conjecture above is not true.…”
Section: Presentations Of a Numerical Semigroupmentioning
confidence: 99%